Numerical investigation of fiber orientations and homogeneity in powder bed fusion of fiber/polymer composites - Tan, Pengfei (2023)
The packing characteristics of fiber/polymer powder in powder bed fusion additive manufacturing exhibit a high correlation with the mechanical behaviours of printed composite parts such as homogeneity and anisotropy. A discrete element model has been developed to investigate the packing characteristics of glass fiber/polyamide 12 (PA12) powder, which include fiber orientations, fiber homogeneity, and packing density. The predicted probability distributions of fiber orientations in the powder bed are comparable with those measured in glass fiber–reinforced PA12 composites printed via multi jet fusion. Three types of fibers with different length distributions are adopted to study the effects of the fiber length distribution on their packing characteristics. The simulation results reveal that a large average fiber length is beneficial to fiber alignment in the powder spreading direction but lowers the fiber homogeneity and packing density of the powder bed. Furthermore, varying the fiber length can provide an effective way to regulate fiber orientations in the powder packing process, which would help achieve satisfactory anisotropic mechanical properties for composite parts.